Green Energy Consumption and Inclusive Growth: A Comprehensive Analysis of Multi-Country Study - Ghouse, Ghulam; Aslam, Aribah; Bhatti, Muhammad Ishaq (Frontiers in Energy Research, 2022)
Better energy uses such as that of ‘green energy’ offer a potential way to resolve the myriad problems involved in environmental degradation, and at the same time help with economic growth. We present two theoretically novel frameworks for understanding the "green energy-growth paradox". First, we build upon the theoretically strong literature while looking for potential explanations for the key determinants, particularly the use of green energy, inclusive growth which means all people in society advancing socio-economically, while also referring to post-COVID-19 data. Second, we carefully examine the key elements of inclusive growth and how they differ in different income groups; which we segregate as low-, middle- and high-income countries using the World Bank’s definition. The inclusive growth index serves as the typical benchmark used in assessing and comparing if green energy use is helping countries with different income levels achieve inclusive growth. The study is a pioneer analysis explores and compares the interesting impacts of green energy use on inclusive growth in global data from the designated income groups.